Integrating Behaviorist and Cognitive Approaches in Qur’anic Learning: A Theoretical and Comparative Literature Study - Abdulloh; Ahmad Yusam Thobroni; Achmad Alhady Ahdan; Alif Akbar Hidayatullah (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
Qur’anic learning holds a central role in Islamic education, aiming not only to instill religious values but also to shape the spiritual character of students. However, to achieve these objectives effectively, educators must adopt appropriate teaching approaches. This study explores the integration of behaviorist and cognitive approaches in Qur’anic learning through a theoretical and comparative literature review. Using relevant academic sources such as books, peer-reviewed journals, and scholarly articles, this research analyzes the characteristics, strengths, and limitations of both approaches. The findings reveal that the behaviorist approach emphasizes repetition, reinforcement, and habit formation, making it effective for memorization and recitation. Meanwhile, the cognitive approach promotes comprehension, reflection, and contextual understanding, which are crucial for meaningful engagement with the Qur’an. Integrating both approaches offers a more holistic model that balances technical mastery and deep understanding. The study concludes that such integration enhances the effectiveness of Qur’anic pedagogy by combining structured reinforcement with active intellectual engagement. This research contributes to the development of more comprehensive and adaptive Qur’anic teaching methods, encouraging educators to design instructional strategies that nurture both the memorization and internalization of Qur’anic values in daily life.